Competence, Work Coordination, Application of Information Technology, Compensation, and Work Environment on Goods/Services Procurement Committee’s Work Performance - Ratnasari, Sri Langgeng; Purnomo, Asep Tomi; Susanti, Ervin Nora; Susanto, Alpino; Sutjahjo, Gandhi; Winarso, Widyo (International Conference on Business Management and Accounting, 2023)
This research is intended to test and analyze the influence of competence, work coordination, application of information technology, compensation, and work environment on the work performance of good/services procurement committee in BP Batam partially and simultaneously. The goods/services procurement committee are those who are working in BP Batam consists of 3 parties; Pejabat Pembuat Komitmen abbreviated as PPK (commitment-making officer), Kelompok Kerja Pemilihan abbreviated as Pokmil (election working group), and Pengadaan Barang/Jasa Pemerintah abbreviated as PBJ (goods/service procurement). The research approach is descriptive quantitative with multiple linear regression analysis techniques. The population in this research is all of the staffs collaborated into the goods/services procurement activities. The sample in this research was selected based on a purposive sampling method. 79 staffs were selected consisting of PPK, Pokmil, and PBJ staffs. The results generally revealed that the work performance of goods/servies procurement committee is proven to be influenced by competence, work coordination, application of information technology, compensation, and work environment. Partially it can also be stated that competency, work coordination, application of information technology, compensation, and work environment have a positive influence on the work performance of goods/services procurement committee with a correlation rate of 64.3% based on the adjusted R square value.